Kidney Histopathology of Wistar Rats Chronic Apical Periodontitis - Sudimartini, Luh Made; Bhala, Anastasia; Wirata, I Wayan; Setiasih, Ni Luh Eka; Widiadnyani, Ni Kadek Eka; Merdana, I Made (Advances in Tropical Biodiversity and Environmental Sciences; Vol 6 No 2 (2022): ATBESDO - 10.24843/ATBES.2022.v06.i02.p04, 2022)
Chronic apical periodontitis is an inflammatory disease that causes periodontal tissue destruction and forms chronic lesions. This study aims to prove that the administration of green meniran leaf ethanol extract can affect the kidney histopathology of chronic apical periodontitis Wistar rats. This study used a randomized posttest only control group design with four treatment groups and twelve replications of three sub-groups according to the time of application of the medicament paste, namely the 7th, 14th, and 21st days so that 48 Wistar rats were used. The treatment group consisted of negative control (K1), only injected with disease-causing bacteria. The positive control group was given 2% Calcium Hydroxide and Chlorhexidine digluconate. Treatment group 1(P1) was given calcium hydroxide and 10% green meniran leaf ethanol extract, and treatment group 2(P2) was given calcium hydroxide, 2% chlorhexidine digluconate, and 10% green meniran leaf ethanol extract. All samples were male Wistar rats with a weight ranging from 300-350 grams. The variables observed were congestion and necrosis with a score of 0 (normal); 1 (focal); 2 (multifocal); 3 (diffuse). The data were analyzed using the Kruskal-Wallis non-parametric statistical test and if it showed a significant effect, it was continued with the Mann-Whitney test. The results of the Kruskal-Wallis test showed that in the K2, P1, and P2 treatments, there was a significant difference (P<0.05) in the category of congestion and necrosis of the histopathological changes of the kidneys. The results of this study indicate that the ethanol extract of green meniran leaves which has a function as an antioxidant can repair kidney damage caused by free radicals in chronic apical periodontitis conditions